Survival for 38 years with Animal-type malignant melanoma (Journal of Pathology of Nepal, 2014)
Animal-type melanoma is a low-grade malignant tumor with a good prognosis. Although it is common in old grey horses, the tumor is exceedingly rare in humans. Only 173 cases have been reported till 2011. We report a case in a 38-year-old woman who had the neoplasm in the left labium majus since birth. The tumor was composed of heavily melanized polygonal tumor cells with mildly atypical nuclei proliferating diffusely and in nests in the dermis and subcutis with invasion of hair follicles and nerve bundles. Mitotic figures were not seen. Regional lymph nodes were not enlarged. Present case describes a patient with animal-type melanoma who has had the lesion since birth and who is still living despite having the tumor for 38 years. It attests to the fact that this tumor has indolent biologic behaviour despite being malignant. Mistaking this case for other highly pigmented melanocytic tumors, benign or malignant, is a potential diagnostic pitfall.DOI: http://dx.doi.org/10.3126/jpn.v4i8.11599 Journal of Pathology of Nepal; Vol.4,No. 8 (2014) 685-687